A simple and fast quantitative analysis of quinolizidine alkaloids and their biosynthetic precursor, lysine, in Sophora alopecuroides by hydrophilic interaction chromatography coupled with triple‐quadrupole tandem mass spectroscopy. Issue 5 (24th March 2018) - Wang, Hanqing; Xiao, Dong; Li, Wei; Zhang, Xia; Gao, Xiaojuan; Yong, Jingjiao; Zhao, Jianjun; Koike, Kazuo
Abstract: Introduction: Different parts of Sophora alopecuroides L. (Fabaceae) have historically been used in traditional Chinese medicine for the treatment of dysentery and enteritis. This plant is also utilised as an important resource for industrial preparation of quinolizidine alkaloidal pharmaceuticals. Objective: Establish a reliable, simple and fast analytical method for the quantitative determination of the quinolizidine‐type alkaloids and extend understanding of the metabolism of quinolizidine‐type alkaloids in S. alopecuroides . Methods: Hydrophilic interaction chromatography coupled with triple‐quadrupole tandem mass spectrometry (HILIC‐TQ‐MS/MS) in multiple‐reaction monitoring (MRM) mode were used to determine seven quinolizidine‐type alkaloids and their biosynthetic precursor, lysine, in S. alopecuroides . Results: A good separation was obtained on an ultra high‐performance liquid chromatography (UHPLC) amide column within 7 min. The overall limits of detection (LODs) were between 1.13 and 2.81 ng/ml, and limits of quantitation (LOQs) were between 3.80 and 8.48 ng/ml. The developed method was successfully applied to 21 samples of S. alopecuroides . The seeds had the highest concentration of alkaloids among the different plant parts. Oxymatrine and oxysophocarpine were the two most abundant alkaloids in all of the different parts and at different phenological growth stages. The contents of quinolizidine alkaloids showed correlations with lysine. Conclusion: A rapid and sensitive analytical method was established for the simultaneous determination of seven quinolizidine‐type alkaloids and their biosynthetic precursor, lysine, in S. alopecuroides ; the content of lysine may be used as a marker to predict alkaloid production. Abstract : A rapid and sensitive analytical method by hydrophilic interaction chromatography coupled with triple‐quadrupole tandem mass spectrometry (HILIC‐TQ‐MS/MS) in multiple‐reaction monitoring (MRM) mode was established for the simultaneous determination of seven quinolizidine‐type alkaloids and their biosynthetic precursor, lysine, in Sophora alopecuroides. The method was successfully applied to 21 samples of S. alopecuroides. The contents of quinolizidine alkaloids showed correlations with lysine, suggesting that lysine may be used as a marker to predict alkaloid production.